The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.foostr.2019.100128
|View full text |Cite
|
Sign up to set email alerts
|

Planar sucrose substrates for investigating interfaces found in molten chocolate

Abstract: We present planar substrates suitable for investigating the sucrose/triglyceride fat interfaces found in molten chocolate with surface science techniques. The planar sucrose substrates are produced by spin coating sucrose onto hydrophilic, silicon oxide-capped, silicon substrates from millimolar aqueous solutions of sucrose. We present the characterisation of the sucrose film thicknesses and crystallinity using X-ray reflectivity and grazing incidence X-ray diffraction, respectively. These sucrose-coated subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, the situation of these two moduli was reversed when the frequency became higher than 1 Hz and subsequently, the loss modulus rose more than storage modulus. tan δ < 1 it behaves like an elastic (Manasi, 2019;Qaiser et al, 2021).…”
Section: Rheological Descriptionmentioning
confidence: 99%
“…However, the situation of these two moduli was reversed when the frequency became higher than 1 Hz and subsequently, the loss modulus rose more than storage modulus. tan δ < 1 it behaves like an elastic (Manasi, 2019;Qaiser et al, 2021).…”
Section: Rheological Descriptionmentioning
confidence: 99%
“…The expected molecular shape of PGPR is distinct from the other surfactants, as the presence of hydroxyl groups on the polyglycerol backbone and terminal ricinoleic acid moieties and ester groups may contribute to a more extended contact area with the sugar crystal surface. It being most effective at high concentrations was indicative of its tendency to produce larger supramolecular structures that provided steric repulsion, resulting in reduced interaction between sugar crystals, as observed by Dedinaite and Campbell 58 and Manasi (2019), who also demonstrated the ability of PGPR to form aggregates localized at the sugar surface that trap oil and provide steric repulsion, which they associated with a decrease in viscosity and yield.…”
Section: Formation Of Supramolecular Structuresmentioning
confidence: 79%
“…Based on the calculated HLB (Table 4) and theoretical geometric molecular shape based on P (Figure 12), CITREM would be expected to form different structures when used in excess vs. lecithin or AMP. Based on Manasi's work 25 , lecithin would form inverse cylindrical micelles at high local concentrations, which would contribute to greater interactions with sugar crystals, supporting the increased adhesion force, apparent viscosity, and sedimentation rate at high concentrations. AMP would similarly form inverse micelles due to the smaller head group.…”
Section: Formation Of Supramolecular Structuresmentioning
confidence: 90%
See 1 more Smart Citation
“…Researchers reported that the optimized linseed spread behaves like a viscous material when the tan δ > 1. On the other hand, when tan δ < 1, it behaves like an elastic matter (Manasi, 2019 ; Qaiser et al, 2021 ). These findings can be explained by the fact that the RLP plays a dual role in the formulation of LS and acts as a filler in the complicated network of the resulting spread.…”
Section: Resultsmentioning
confidence: 99%